Denosumab in patients with osteogenesis imperfecta and a historical control study with alendronate - Mei, Yazhao; Cai, Shiya; Jiang, Yunyi; Tian, Yuan; Shen, Li; Gu, Jiemei; Wang, Chun; Zhang, Zhenlin; Zhang, Hao (Frontiers in Endocrinology, 2025)
PurposeOptimal dosing of denosumab in osteogenesis imperfecta (OI) remains undefined. This prospective cohort study evaluated the 12-month efficacy and safety of denosumab in OI patients, with a historical control study with alendronate.Materials and methodsEight pediatric patients (1 mg/kg every 3 months; ≤60 mg/dose) and ten adults (60 mg every 6 months) received denosumab. Outcomes included lumbar spine (LS) and femoral neck (FN) bone mineral density (BMD), bone turnover markers (BTMs), vertebral compression fractures (assessed via AI-assisted Genant grading [AI_OVF_SH system]), fracture incidence, height velocity and adverse events. Historical controls (n=25 alendronate-treated OI patients) were analyzed for comparative efficacy. Sensitivity analyses excluded female pediatric participants (n=4) and peri-/post-menopausal adults (n=4) to assess hormonal confounding.ResultsPediatric denosumab recipients exhibited significant LS-BMD (+30.3%, P<0.001) and FN-BMD gains (+38.7%, P=0.001) versus baseline, whereas adults showed non-significant increases (LS: +2.6%, P=0.100; FN: +4.4%, P=0.051). Sensitivity analyses revealed attenuated BTMs suppression in adults after excluding peri-/post-menopausal women (only ALP decreased by 27.9%, P=0.028). Rebound hypercalcemia occurred in 62.5% (5/8) of children, peaking at 2.93 mmol/L. Compared to alendronate, denosumab demonstrated comparable BMD improvements and fracture reduction (P>0.050) but superior pediatric height gain (+5.8% vs. +2.5%, P=0.004). Vertebral area loss decreased significantly with denosumab (-14.6%, P=0.029), unlike alendronate (-8.8%, P=0.296). Adverse events were more frequent with denosumab in children (hypercalcemia: 62.5% vs. 0%, P=0.002).ConclusionDenosumab demonstrates non-inferior efficacy to alendronate for BMD improvement in OI, with heightened vertebral remodeling and pediatric height gains. However, its overshoot phenomenon in children (rebound hypercalcemia) and hormone-dependent efficacy in adults necessitate risk-stratified use. Age and menopausal status considerations are critical for optimizing denosumab therapy in OI.Clinical trial registrationhttps://www.chictr.org.cn/bin/project/edit?pid=184231, identifier ChiCTR2300074207.